Factors Associated with Malnutrition among Newly Diagnosed Esophageal Cancer Patients - Yi, Ho Chiou; Kahairudin, Zuliehaiza; Musa, Aini; Mohd Haniff Lai, Betti Sharina; Kay, Neoh May; Han, Ng Wai; Zakaria, Nor Adlina; Mohd Samwil, Siti Nuraini; Abdullah, Aeininhayatey; Pardi, Munawara; Jamhuri, Norshariza (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
The study aimed to investigate the factors associated with malnutrition among newly diagnosed EC patients. A cross-sectional study included newly diagnosed EC patients from October 2020 to March 2022. Data on clinical status (diagnosis, comorbidities, and cancer stage), socio-demographic characteristics, functional status [Performance status scale using Eastern Cooperative Oncology Group (ECOG)], anthropometric measures [weight, height, and percentage of weight loss (% LOW) past 1-month], biochemical profiles [lymphocyte and serum albumin], malnutrition status [Subjective Global Assessment (SGA)] and total daily energy protein intake were assessed. The study enrolled 227 participants, and 96.5% (n=219) were malnourished. The mean for age, weight, percentage of weight loss past 6-months, SGA score, total daily energy protein intake, and serum albumin were 61.1±11.4 years, 57.7±14.4 kg, -8.6±6.5%, 12.6±3.9, 17±5 kcal/kg/day, 0.7±0.1 g/kg/day, and 35±5 g/L respectively. About 80.6% were stage III and IV, 96% experienced dysphagia, and 67% experienced muscle wasting. The % LOW past 1 month, gender, ECOG status, and lymphocyte levels were found to be the significant factors related to malnutrition among newly diagnosed EC patients (p<0.05) by a multi-linear regression test. EC patients are at high risk of being malnourished as the tumor-related symptoms include dysphagia, inadequate nutritional intake, muscle wasting, and lymphocytopenia. The current study is restricted to only one-time nutritional screening and evaluation. The current proposed model of malnutrition is a simple, useful, and efficient clinical tool to identify EC-related malnutrition followed by the early multidisciplinary-team approach-based nutrition intervention to minimize nutrition depletion, improve functional status, and enhance clinical outcomes before therapy or even higher survival rate.